PENGARUH ETOS KERJA, DISIPLIN KERJA DAN KOMITMEN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PUSKESMAS ARO KECAMATAN MUARA BULIAN - Rosmawati, Sri; Jermawinsyah, Ade (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
This study aims to determine the effect of work ethics, work discipline and employee commitment at Aro Puskesmas in Muara Bulian District. This study included descriptive verification research. The population of this study was 56 people. By using a Likert scale, it shows the variables of work ethics, work discipline and employee commitment are in a good category. And multiple regression to determine the relationship of work ethic, work discipline and employee commitment to the Aro Health Center in Muara Bulian District. The results of the study and discussion show that work ethic has a negative effect on employee performance, while work discipline variables and employee commitment variables have a positive effect on employee performance at Aro Health Center in Muara Bulian District. Simultaneously shows that work ethics, work discipline and employee commitment show an influence on employee performance. With the value of R Square of 0.725, this shows that work ethic, work discipline and employee commitment affect work performance as much as 72.5% and the rest is influenced by other variables not examined in this study.